COOPERATIVE TAKAFUL MODEL: A NEW GAME CHANGER (Revista Galega de Economía)
Purpose- Though the takaful industry is undergoing a period of rapid development and growth, it has been seen to be too commercialised and the mutually spirit was seen disappeared. On the other hand, it faces many critics for imposing terms and conditions that benefitted takaful operators and not sufficient to cover the needs of the participants. Therefore, the study aims to analyse an alternative model to takaful industry in Malaysia using cooperative takaful model by analysing the mutuality and cooperative concept and discussing few controversial issues related to existing takaful model.